THE DEVELOPMENT OF CURVED SIDE CONSTRUCTION LEARNING MEDIA INVOLVING PROBLEM SOLVING CAPABILITY AND LOCAL CULTURE WISDOM - Nur, Andi Saparuddin; Dadi, Oswaldus (JPI (Jurnal Pendidikan Indonesia), 2018)
The purpose of this study was to obtain a learning tool of curved side room learning materials based problem-solving ability and local cultural wisdom for students of class IX Junior High School in Merauke City that meet valid, effective, and practical criteria. This type of research is development research with 4D model design (Define, Designed, Develop, Disseminate). The subjects of the study were the students of class IX of SMP Negeri 9 Merauke. The resulting learning tools were tested and experimented using the posttest only control group design. The result of this research is obtained learning tools of curved side room learning-based problem-solving ability and local cultural wisdom that fulfill valid, practical, and effective criteria. Learning tools produced are student books, Student Activity Sheets (LKS), and Lesson Plans (RPP). The results of the device test show the students' mathematics problem-solving ability is better than the control class with an average score of 61.81 versus 52.57. Hypothesis testing using independent sample t-test shows Ho is rejected with the t count value of 3.049 which means that problem-solving ability using local culture learning tools is better using conventional learning devices.